PELAKSANAAN PENGELOLAN ARSIP DINAMIS DI DINAS KEARSIPAN DAN PEPRUSTAKAAN KABUPATEN SUKOHARJO - Heni Mardiana Rahayu; Wiedy Murtini; Susantiningrum Susantiningrum (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
Abstract This study aims to determine: 1) dynamic archive processing in the Archives and Library Office of Sukoharjo; 2) constraints that occur in the processing of dynamic archives; 3) solutions given to the problems that occur. This research is a qualitative research with a case study approach. Sources of research data include informants, documents, and events. The sampling technique was carried out by purposive sampling and snowball sampling. Data was collected by means of interviews, observations, and documents. The validity test technique used is triangulation of techniques and sources. Data analysis techniques with interactive analysis techniques. The results of the study are as follows: 1) dynamic archive processing is still not optimal: (a) lack of maintenance kept so that there are damaged records; (b) lack of supervision over the distribution of incoming mail; (c) There are still many archives that have not been processed; (d) Retrieval of archives often experiences problems, namely the archives to be borrowed are lost or damaged; 2) lack of facilities, infrastructure, and the limited number of workers owned so that it hampers the processing of dynamic archives.